Wokół premierostwa Felicjana Sławoja Składkowskiego. Uwagi i spostrzeżenia - Adamczyk, Arkadiusz (Acta Universitatis Lodziensis. Folia Historica, 1997)
Many of his contemporaries as well as many present-day historians considered F. Sławoj Składkowski to be incompetent to manage government affairs. Prime Minister’s lack of political independence and performing some actions exceeded his regular duties became the main points of the accustations against him. These opinions, however, did not take into an account of political conditions, which had occured after Piłsudski’s death. In such eventful period, F. Sławoj Składkowski turned out to be an efficient Prime Minister and his cabinet the longest active of inter-war Poland.